RENCANA BISNIS CC FLORIST & DECORATION - Clara Cornelia; Petrus Pius Salamin (Prosiding Working Papers Series In Management, 2017)
CC Florist & Decoration is a business engaged in the creative fashion industry. CC Florist & Decoration business providing fresh flower with flower arrangement as per customer's request and wish. CC Florist & Decoration has the vision to be a leading florist producer with excellence in material quality, state of the art, luxury and splendor of floral decoration making it an unforgettable experience for CC Florist & Decoration customers. CC Florist & Decoration has the mission to be flower arranging in accordance with the wishes of consumers, ensure freshness of the flowers are maintained until the hands of consumers, and speed responds in ordering process and delivery of flower arrangement. The market opportunity of CC Florist & Decoration is that the first year's sales interest is estimated at Rp676.734.000,00 and will increase to Rp2.451.184.687,00 in 2022, with sales growth rates ranging from 20% to 40% by 2022. CC Florist & Decoration Market Strategy is Major market targets; Event Organizer, Wedding Organizer, and Jakarta people who need interest in various events and daily in DKI Jakarta area, Product strategy; provides fresh flowers of good quality and has a variety of products that consumers can choose from, Price strategy; determining the selling price based on Penetration Price, Promotional strategies; advertising, brochures, social media marketing, edorsement, and sales promotion, Distribution channels; through online ojek application as well as courier CC Florist & Decoration. CC Florist & Decoration Financial Target is The need for investment funds and working capital amounted to Rp112.400.000,00. With a profit rate of Rp41,007,910.00 in 2018 and increased to Rp297.411.586,00 in 2022 with a growth rate of between 20% to 40% every year. Keywords: CC Florist & Decoration